ĐÁNH GIÁ KHẢ NĂNG ỨC CHẾ ĂN MÒN THÉP VÀ NHÔM CỦA MỘT SỐ DÃY HỢP CHẤT AZOMETIN - Phạm, Duy Nam; Nguyễn, Văn Ngọc; Nguyễn, Đình Thành; Đặng, Như Tại (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
CORROSION INHIBITION EFFICIENCIES OF SCHIFF’S BASES ON MILD STEEL AND ALUMINIUMThe corrosion inhibition efficiencies of 39 Schiff’s bases of series from aniline, ethylendiamine, cyclohexylamine and 4,4 benzidine in the 1M and 2M HCl solutions on the steel (CT-3) and aluminium (D16) have been studied. It seems that the azomethine compounds with aldehyde moieties of 3-indolyl group (B8, C8 and H8) strongly inhibited the corrosion on aluminium but the corrosion inhibition effects on steel are relatively low. The azomethine compounds with aldehyde moieties of p-nitrophenyl group (B1, C1 and H1) inhibited highly the corrosion of both steel and aluminium in HCl solution. The bis-(4-nitrobenzylidene) diethylamine (B1) compound can be used as a good corrosion inhibitor for low carbon steel and aluminium in HCl acid solution.